Acute Heart Failure in the 2021 ESC Heart Failure Guidelines: a scientific statement from the Association for Acute CardioVascular Care (ACVC) of the European Society of Cardiology. Issue 2 (18th January 2022) - Masip, Josep; Frank Peacok, W; Arrigo, Mattia; Rossello, Xavier; Platz, Elke; Cullen, Louise; Mebazaa, Alexandre; Price, Susanna; Bueno, Héctor; Di Somma, Salvatore; Tavares, Mucio; Cowie, Martin R; et al.
Abstract: The current European Society of Cardiology (ESC) Heart Failure Guidelines are the most comprehensive ESC document covering heart failure to date; however, the section focused on acute heart failure remains relatively too concise. Although several topics are more extensively covered than in previous versions, including some specific therapies, monitoring and disposition in the hospital, and the management of cardiogenic shock, the lack of high-quality evidence in acute, emergency, and critical care scenarios, poses a challenge for providing evidence-based recommendations, in particular when by comparison the data for chronic heart failure is so extensive. The paucity of evidence and specific recommendations for the general approach and management of acute heart failure in the emergency department is particularly relevant, because this is the setting where most acute heart failure patients are initially diagnosed and stabilized. The clinical phenotypes proposed are comprehensive, clinically relevant and with minimal overlap, whilst providing additional opportunity for discussion around respiratory failure and hypoperfusion.